Anti-Covid-19 Phytochemicals - Pawar, Rajendra Singh; Dimri, Mayank; Maithani, Alok; Kush, Luv (Asian Journal of Pharmaceutical Research and Development, 2020)
The Phytochemicals are the future phytomedicine for Covid-19 virus, therefore their antiviral affinity was differently viewed.